Pipelines 2019 : Planning and Design. - Heidrick, Jeffrey W. (American Society of Civil Engineers, 2019)
This collection contains 40 peer-reviewed papers on the planning and design of pipelines presented at Pipelines 2019, held in Nashville, Tennessee, July 21-24, 2019.